2011
DOI: 10.1007/s10875-011-9617-4
|View full text |Cite
|
Sign up to set email alerts
|

Radioligand-Binding Assay Reveals Distinct Autoantibody Preferences for Type I Interferons in APS I and Myasthenia Gravis Subgroups

Abstract: Patients with autoimmune polyendocrine syndrome type I (APS I) or acquired thymoma-associated myasthenia gravis (MG) surprisingly share several common features, including defective expression of the transcription factor AIRE and autoantibodies against type I interferons. Here, we have adapted and validated the radioligand-binding assay we recently developed against (35)S-Met-interferon-ω, for rapid and specific screening for autoantibodies against interferons-α2 and -α8. We then investigated their potential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…Sequencing identified two heterozygous mutations in this patient. IFN‐ω and IFN‐α antibodies were detected in isolated cases of PAI in two other studies . AIRE mutations were either absent or not studied in these patients.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Sequencing identified two heterozygous mutations in this patient. IFN‐ω and IFN‐α antibodies were detected in isolated cases of PAI in two other studies . AIRE mutations were either absent or not studied in these patients.…”
Section: Discussionmentioning
confidence: 76%
“…IFN-x and IFN-a antibodies were detected in isolated cases of PAI in two other studies. 35,36 AIRE mutations were either absent 35 or not studied 36 in these patients.…”
Section: Discussionmentioning
confidence: 86%
“…In a further study, the same research group, utilizing a radioligand-binding assay, confirmed that Abs to IFN- ω occur in the totality of APS-1 patients and beat the prevalence of Abs to two subtypes of IFN- α , namely IFN- α 2 and IFN- α 8 , that in turn are found in a high percentage of patients with thymoma-associated myasthenia gravis [84]. …”
Section: Thymic Diseases and Aire Expression In Human Fieldmentioning
confidence: 95%
“…The first disease components, most usually chronic mucocutaneous candidiasis and hypoparathyroidism, normally emerge in childhood, but the heterogeneity of APECED in terms of its initial clinical presentation can make it challenging to identify and, typically, the condition is diagnosed after the first decade of life 1 , 5 . More recently, the presence of antibodies against interferon (IFN)- ω and IFN- α 2 has been shown to aid diagnosis due to their sensitivity and relative specificity for APECED 6 , 7 . Anti-interleukin (IL)-22, anti-IL-17A, and anti-IL-17F antibodies are also common 8 .…”
Section: Introductionmentioning
confidence: 99%